2022
DOI: 10.17130/ijmeb.982102
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Impulsive Buying Behaviour and a Model Proposal

Abstract: Impulsive buying is a sudden, unplanned purchase that the consumer makes without thinking about the consequences. Impulsive buying has become an important economic phenomenon due to the availability of credit cards, the existence of online shopping options, and the spread of shopping mall culture. This study investigates the effects of social media, hedonic consumption and conscientiousness on the impulsive buying behaviour of consumers in the city of Ankara, Turkey. Data were collected through face-to-face i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 27 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…The study unfolds that there are several factors that affect women's impulsive shopping behaviour such as attractive display of clothing, buy one get one offer, discounted price, well decorated shop, gift giving, sales representatives' behaviour, exchange offer, membership discount and bundle offer. This finding closely supports that of Kurt, Kardiyen & Bakir (2022) that store display, in-store promotion, store employees' friendly behaviour, discount, gifts, exchange option, membership discount affect an individual's desire to buy an item impulsively. After analysing the data, it has been found that there is a moderate association between dependent variable and independent variables.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…The study unfolds that there are several factors that affect women's impulsive shopping behaviour such as attractive display of clothing, buy one get one offer, discounted price, well decorated shop, gift giving, sales representatives' behaviour, exchange offer, membership discount and bundle offer. This finding closely supports that of Kurt, Kardiyen & Bakir (2022) that store display, in-store promotion, store employees' friendly behaviour, discount, gifts, exchange option, membership discount affect an individual's desire to buy an item impulsively. After analysing the data, it has been found that there is a moderate association between dependent variable and independent variables.…”
Section: Resultssupporting
confidence: 83%
“…A well decorated shop often might not have attractive display of product. Lighting, painting, cleanliness, background music and smell altogether make well decoration whereas attractive display of product such as clothing needs careful assortment, use of mannequins, display shelves, tables, and wall space (Kurt, Kardiyen & Bakir, 2022). A well decorated shop can keep the consumer for a long time within the store whereas an attractive display of product persuades the consumer to be more close to the product and generate more impulse buying (Guenzi, Johnson & Castaldo, 2009).…”
Section: H 5: Membership Discount Positively Affects Women Impulse Bu...mentioning
confidence: 99%
See 1 more Smart Citation